Sialylation of EGFR by the ST6Gal-I sialyltransferase promotes EGFR activation and resistance to gefitinib-mediated cell death - Colleen M. Britain; Andrew T. Holdbrooks; Joshua C. Anderson; Christopher D. Willey; Susan L. Bellis (Journal of Ovarian Research, 2018)
Abstract Background The ST6Gal-I sialyltransferase is upregulated in numerous cancers, and high expression of this enzyme correlates with poor patient prognosis in various malignancies, including ovarian cancer. Through its sialylation of a select cohort of cell surface receptors, ST6Gal-I modulates cell signaling to promote tumor cell survival. The goal of the present study was to investigate the influence of ST6Gal-I on another important receptor that controls cancer cell behavior, EGFR. Additionally, the effect of ST6Gal-I on cancer cells treated with the common EGFR inhibitor, gefitinib, was evaluated. Results Using the OV4 ovarian cancer cell line, which lacks endogenous ST6Gal-I expression, a kinomics assay revealed that cells with forced overexpression of ST6Gal-I exhibited increased global tyrosine kinase activity, a finding confirmed by immunoblotting whole cell lysates with an anti-phosphotyrosine antibody. Interestingly, the kinomics assay suggested that one of the most highly activated tyrosine kinases in ST6Gal-I-overexpressing OV4 cells was EGFR. Based on these findings, additional analyses were performed to investigate the effect of ST6Gal-I on EGFR activation. To this end, we utilized, in addition to OV4 cells, the SKOV3 ovarian cancer cell line, engineered with both ST6Gal-I overexpression and knockdown, as well as the BxPC3 pancreatic cancer cell line with knockdown of ST6Gal-I. In all three cell lines, we determined that EGFR is a substrate of ST6Gal-I, and that the sialylation status of EGFR directly correlates with ST6Gal-I expression. Cells with differential ST6Gal-I expression were subsequently evaluated for EGFR tyrosine phosphorylation. Cells with high ST6Gal-I expression were found to have elevated levels of basal and EGF-induced EGFR activation. Conversely, knockdown of ST6Gal-I greatly attenuated EGFR activation, both basally and post EGF treatment. Finally, to illustrate the functional importance of ST6Gal-I in regulating EGFR-dependent survival, cells were treated with gefitinib, an EGFR inhibitor widely used for cancer therapy. These studies showed that ST6Gal-I promotes resistance to gefitinib-mediated apoptosis, as measured by caspase activity assays. Conclusion Results herein indicate that ST6Gal-I promotes EGFR activation and protects against gefitinib-mediated cell death. Establishing the tumor-associated ST6Gal-I sialyltransferase as a regulator of EGFR provides novel insight into the role of glycosylation in growth factor signaling and chemoresistance.